Kapili wall of the side shrine of the Triple-shrine Temple - Temples of India Project Team (Jio Institute, 2024)
The kapili wall of the side shrine of the Triple-Shrine Temple has a small low-relief devakoshtha (niche) with the depiction of the couple. This wall portion has small aedicules as the shikhara (superstructure), which are similar to the tiers of the main shikhara. The kapili has a ceiling wall connected to it which cantilevers to its east side. This is supported by two slender pillars having a ghatapallava (vase with foliage) motif.